2001
DOI: 10.1021/ci010076u
|View full text |Cite
|
Sign up to set email alerts
|

4D-QSAR Analysis of a Set of Ecdysteroids and a Comparison to CoMFA Modeling

Abstract: The ecdysteroid-responsive Drosophila melanogaster B(II) cell line is a prototypical homologous inducible gene expression system. A training set of 71 ecdysteroids, for which the -log(EC(50)) potencies in the ecdysteroid-responsive B(II) cell line were measured, was used to construct 4D-QSAR models. Four nearly equivalent optimum 4D-QSAR models, for two modestly different alignments, were identified (Q(2) = 0.76-0.80). These four models, together with two CoMFA models, were used in consensus modeling to arrive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 55 publications
1
48
0
Order By: Relevance
“…However, a 22-O-benzyl substituent (9) does not significantly decrease 20E potency, a result that recalls by analogy the moderately high responsiveness of the 20E 22-benzoyl derivative. [34] On the other hand, O-alkylation of PoA at any position decreases potency in this bioassay.…”
Section: Synthesismentioning
confidence: 86%
See 2 more Smart Citations
“…However, a 22-O-benzyl substituent (9) does not significantly decrease 20E potency, a result that recalls by analogy the moderately high responsiveness of the 20E 22-benzoyl derivative. [34] On the other hand, O-alkylation of PoA at any position decreases potency in this bioassay.…”
Section: Synthesismentioning
confidence: 86%
“…Estimation of ADME properties: The 1-octanol-water partition coefficients (Mlog P) [80] of ecdysteroid O-alkyl ether analogues were determined by scaling against previously calculated [34] Mlog P values of nonether ecdysteroids. Estimations of the Caco-2 cell permeation coefficients and the blood-brain barrier partition coefficients, were made using established membrane-interaction QSAR (MI-QSAR) models.…”
Section: Physicochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D). Thus, dhMaA is a fully functional ecdysteroid in vivo, whereas 24-epi-MaA suffices for larval stages, but cannot support pupal development, consistent with its lower activity in tissue culture assays (Clément et al, 1993;Ravi et al, 2001). Thus, the ability of yeast-fed animals to selectively utilize 24 (28)-dehydroergosterol(s) for dhMaA synthesis is likely to be crucial for survival when feeding on yeast in the wild.…”
Section: Individual Sterols Give Rise To Different Ecdysteroidsmentioning
confidence: 88%
“…15,16 The data obtained from such studies have led to a pharmacophore hypothesis for the interactions of ligands with the ecdysteroid receptor: it is postulated that the key molecular features responsible for the activity are not identical to the characteristic structural elements mentioned above. The structure-activity studies have revealed that a hydroxy group on C-2 acts as an H-bond acceptor, C-3 should be substituted, preferably with a polar negative atom, a hydroxy group on C-20 is an H-bond donor and a hydroxy group on C-22 is an H-bond acceptor.…”
Section: Structural Diversity Of Ecdysteroidsmentioning
confidence: 99%